Efektifitas Abu Sekam Padi Dan Poly Aluminium Chloride Dalam Menurunkan Zat Warna Limbah Cair Industri Sasirangan - Luqman Nur Hakim; Syarifudin A.; Sulaiman Hamzani (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2016)
Abstract: Effectiveness Of Rice Husk Ash And Poly Aluminum Chloride In Reducing Exposure Colour Liquid Waste Industry Sasirangan. Sasirangan fabric industry is the textile of industry in Kalimantan Selatan produce wastewater of dyeing cloth sasirangan process that uses water as a primary adjuvant in stage process.The study aims to determine the effectiveness of rice husk ash and Poly Aluminium Chloridereduce levels of dyes in wastewater sasirangan "Oriens Handycraft". This study tested a laboratory scale with dose variation of rice husk ash and Poly Aluminium Chloride for reduced levels of dyes in wastewater sasirangan. The study design is a randomized pretest - posttest control group design. The population of the waste liquid fabric manufacturesasirangan results and samples are the waste from the manufacture of cloth sasirangan which represents the population. This study conduct statistical tests usingKruskal Wallis and Mann-Whitney Test.Theresultsofthestudyof color levels priorto treatment equal to 2,712 PtCo and after treatment ranges from 676.3 to 978.7 PtCo at a dose of 58 grams of rice husk ash; 59 g; 60 g; 61 g; 62 gr and Poly Aluminium Chloride 0.5 gr. For a dose of 58 grams of rice husk ash; 59 g; 60 g; 61 g; 62 gr and Poly Aluminium Chloride 1 g of color levels before treatment and after PtCo 1775 amounted to 227.7 PtCo ranges up to 240 PtCo. Rice husk ash and Poly Aluminium Chloride effective at pH 6.5 - 7. Results of normality test showed abnormal data. Kruskal Wallis test probability value 0.002 <0.05, there is a difference between the average dosing in the control group and the treatment group and the Mann-Whitney Test probability value of 0.009 (0.018 <0.05), the rice husk ash dosing and Poly Aluminium Chloride 1 g more effective than rice husk ash dosing and Poly Aluminium Chloride 0.5 g.Efforts government can do is provide the appropriate policy on effluent quality standards and attention to industrial waste disposal sasirangan. For the industry can manage its waste before waste into the environment. Keywords: SasiranganWaste; Materials coagulant; pH; Dyes